Evaluation of Antibiotic Utilization in a Rural, Outpatient Clinic: An Antimicrobial Stewardship Initiative. (October 2021) - Giles, Amber B.; Sarbacker, G. Blair; Anderson, Kathryn; King, Courtney; Goodbar, Neal; Shealy, Kayce
Background: Antibiotics are commonly prescribed for uncomplicated urinary tract infection (UTI) and acute otitis media (AOM) and may be unnecessary at times. The aim of this study was to evaluate prescribing practices for UTIs and AOM in a rural ambulatory care setting and to identify areas for improvement. Methods: In a single-center, retrospective review conducted at a rural clinic, patients diagnosed with uncomplicated UTI and AOM were included. Patients were identified by International Classification of Diseases, Tenth (ICD-10) codes, and data were collected for visits between January 1, 2017, and December 31, 2017. The primary outcome was to assess adherence of antimicrobial prescribing to current treatment guidelines. Results: Of the 76 patients identified, 28 met inclusion criteria. Of the 28 patients, 75% received an agent recommended first line in the treatment guidelines, and 18 of the 21 received a recommended dose. Only 17% of patients were prescribed an appropriate duration of treatment. Conclusion: Opportunities exist for antimicrobial stewardship interventions for uncomplicated UTIs and AOM. Prescribers are not consistently adhering to guidelines in regard to antibiotic choice, dose, or duration. Additional education and stewardship interventions are crucial considering the increased prevalence of antimicrobial resistance.